1989
DOI: 10.1039/c39890000780
|View full text |Cite
|
Sign up to set email alerts
|

First report of a polymeric peroxide initiated room temperature radical polymerization of vinyl monomers

Abstract: Room temperature radical polymerization of acrylamide, methyl methacrylate, and styrene has been achieved with poly(styrene peroxide)-amine initiator systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 2 publications
0
36
0
Order By: Relevance
“…reaction were feasible with polyperoxides, it In 1989, Mukundan et al 2 have reported that the would result in the formation of a polyether via reaction of polyperoxide with amines, which prothe reorganization of the polymer backbone. ceeds through a radical mechanism, could be exIn this investigation we have attempted to ploited for use as radical initiating system for vistudy the nucleophilic attack of TPP on polyperoxnyl polymerizations.…”
Section: Introductionmentioning
confidence: 98%
“…reaction were feasible with polyperoxides, it In 1989, Mukundan et al 2 have reported that the would result in the formation of a polyether via reaction of polyperoxide with amines, which prothe reorganization of the polymer backbone. ceeds through a radical mechanism, could be exIn this investigation we have attempted to ploited for use as radical initiating system for vistudy the nucleophilic attack of TPP on polyperoxnyl polymerizations.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7][8] Vinyl polyperoxides have generated much interest because of their potential applications for use as auto-combustible polymeric fuels, [9] and initiators and curatives. [10] Poly(styrene peroxides) (PSPs) are used as initiators in preference to the conventional peroxides for the synthesis of novel polymers like interpenetrating networks and comb-polymers. [11] Because of their controlled combustibility by degradation, [8] PSP can also be used as a unique auto-combustible polymer fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The main product of oxidative polymerization is polyperoxide, an alternating copolymer of vinyl monomer and molecular oxygen [1][2][3]. Polyperoxide finds importance as polymeric radical initiators [4][5][6] for vinyl monomers in the synthesis of homopolymers, block copolymers, etc. Their importance as curators in coating and molding applications has been established [7].…”
Section: Introductionmentioning
confidence: 99%